Strategies to Manage Aquifer Recharge in Balochistan, Pakistan: An Overview - Syed Mobasher Aftab; Rehanul Haq Siddiqui; Muhammad A. Farooqui (Advanced Aspects of Engineering Research Vol. 9, 2021)
Balochistan plateau is dominated by the drainage system of eighteen river basins, where precipitation recharges both consolidated and unconsolidated aquifers. In eleven river basins, the groundwater levels are steadily depleting for the last three decades due to indefensible long-term groundwater extraction. The cumulative decline of water-table ranges from 2 to 3 meters/yr. The most significant decrease of 60m in the last 12 years has been recorded in parts of Quetta Valley. The estimated total groundwater recharge in an average year of all river basins is 2,200 Mm3, the withdrawal is 2,657 Mm3. The groundwater overdraft in eleven river basins is 886 Mm3, whereas 429 Mm3 is available for sustainable development only in 7 river basins. To enhance groundwater recharge, many proposals have been advanced, and several studies have been carried out by different public and private sector organizations for the protection of natural resources. However, implementation on the recommendations of these studies remained limited with little progress causing severe shortages of groundwater resources. Assorted strategies have been developed by the concerned government departments for the protection of natural resources under their jurisdiction. A comprehensive provincial policy and subsequent strategy for the protection and sustainable development of natural resources in Balochistan is yet to be formed. In this paper the natural resource protection policies and strategies that are directly or indirectly associated with the surface and groundwater resources have been assessed. In addition, the federal and provincial government’s policies including water, biodiversity, climate change, environment, agriculture, forest, and rangeland management have been reviewed and summarized. In some of the previous strategies, certain measures have been proposed for the sustainability of water resources. The measures include a ban on agriculture tubewells in urban areas, construction of storage, supply, and delay action dams (DADs). As a consequence, 326 DADs with a storage capacity of 332 Mm3 were constructed in different river basins. The studies represent that in current circumstances, the DADs are the appropriate means to recharge aquifers if supported by design modifications and catchment area-specific watershed management plans. For the sustainable management of natural resources of the province, a comprehensive, integrated watershed management strategy and a model are devised.